Comparison of Titratable Oral Appliance and Mandibular Advancement Splint in the Treatment of Patients with Obstructive Sleep Apnea. (9th June 2011) - Sari, Emel; Menillo, Steven
Abstract : Objective. To compare the effect of two intraoral devices (titratable oral appliance-Klearway (KW) and mandibular advancement splint (MAS)) in mild and moderate obstructive sleep apnea (OSA) patients. Method and Materials. The study group was comprised of twenty-four adult volunteer patients with OSA. Twelve subjects were fitted with a titratable oral appliance (group KW) protruding the mandible (85% of maximum protrusion). The other 12 subjects received MAS with 75% protrusion of the mandible (group MAS). Baseline, ("0.PSG"), first week (K1.PSG for KW group and M1.PSG for MAS group), and after the first month (K2.PSG for KW group and M2 ′ . PSG for MAS group). Results. Both groups produced similar reduction in apnea-hypopnea index (AHI) from baseline till the end of the first week and first month (P < .05 ). However, the success rate of both groups at the end of the first month was found to be statistically different from the success rate of the first week (P < .05 ). The reduction in mean AHI of group KW-moderate (KW-mo) was significantly different from the mean AHI of group MAS-moderate (MAS-mo) at the end of the first month (P < .05 ). Conclusion. This study suggests that Klearway appliance was more effective in treating moderate OSA patients than MAS appliance. It was concluded that an appliance that provides 85% mandibular advancement to open the upper airway was more effective in reducing the number of high apneic events during sleep in comparison to the one which provides 75%.